2023
DOI: 10.3390/genes14051057
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Profile and Clinical Characteristics of CRX-Associated Retinopathy in Koreans

Abstract: This study aimed to investigate the clinical characteristics of Korean patients with retinal dystrophy associated with pathogenic variants of cone rod homeobox-containing gene (CRX). We retrospectively enrolled Korean patients with CRX-associated retinal dystrophy (CRX-RD) who visited two tertiary referral hospitals. Pathogenic variants were identified using targeted panel sequencing or whole-exome sequencing. We analyzed clinical features and phenotypic spectra according to genotype. Eleven patients with CRX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…One study reported that all mutations within the homeodomain were missense mutations, with most showing a phenotype of cone-rod dystrophy or macular degeneration. On the other hand, most mutations in other regions of the gene were frame-shift mutations resulting in truncating proteins (88%), associated with different phenotypic presentations (cone-rod dystrophy and macular degeneration in 36%, Leber congenital amaurosis in 40%, and RP in 24%) [17]. Moreover, most mutations occur de novo in the absence of a positive family history [8].…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that all mutations within the homeodomain were missense mutations, with most showing a phenotype of cone-rod dystrophy or macular degeneration. On the other hand, most mutations in other regions of the gene were frame-shift mutations resulting in truncating proteins (88%), associated with different phenotypic presentations (cone-rod dystrophy and macular degeneration in 36%, Leber congenital amaurosis in 40%, and RP in 24%) [17]. Moreover, most mutations occur de novo in the absence of a positive family history [8].…”
Section: Discussionmentioning
confidence: 99%
“…CRX, a cone-rod homeobox-containing gene (OMIM: 602225), encodes a homeodomain transcription factor crucial for the development and survival of photoreceptors [85,86]. CRX-retinopathy encompasses severe AR-LCA, AR-RP, AD-CORD, AD-COD, and AD-MD; AD-MD shows a mild phenotype [39,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101]. The relatively mild phenotype of patients with CRX-OMD is consistent with the previous AD-CRX cases [87], although there are no reported CRX cases with the identical variant.…”
Section: Discussionmentioning
confidence: 99%